Utilization Of Water Fertilizer (Azolla pinnata) As A Liquid Organic Fertilizer In Pakcoy (Brassica rapa L.) - Jonathan Monareh Monareh; Jeanne M. Paulus; Sandra E. Pakasi (Sam Ratulangi University, 2023)
This study aims to determine the effect of POC Azolla on the growth and yield of pakcoy (Brassica rapa L) and to dete rmine the best concentration of POC Azolla on the growth and yield of pakcoy (Brassica rapa L). The type of research used is an experimental method to test the effectiveness of POC Azolla against pakcoy plants. The design used in this study was a completely randomized design (CRD). In this experiment there were 4 treatments and 5 replications, namely P0 = 0 ml/liter of water (without POC), P1 = POC 100 ml/l liter of water, P2 = POC 150 ml/l liter of water, P3 = POC 200 ml/l liters of water. Parameters observed were plant height, number of plant leaves, plant leaf width and fresh weight. Based on the results of research that has been carried out on pakcoy plants using POC azolla with treatment concentrations of P0=POC 0.0ml/liter of water, P1=POC of 100ml/liter of water, P2=POC of 150ml/liter of water and P3=POC of 200ml/liter of water. So it can be concluded that the administration of POC azolla had a significant effect on all parameters, namely plant height, leaf width, number of leaves, and fresh weight of pakcoy plants at 3 WAP to 6 WAP. Keywords: Azolla pinnata, Liquid Organic Fertilizer, Brassica rapa L. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh POC Azolla terhadap pertumbuhan dan hasil tanaman pakcoy (Brassica rapa L) dan untuk mengetahui konsentrasi POC Azolla yang terbaik terhadap pertumbuhan dan hasil tanaman pakcoy (Brassica rapa L). Jenis penelitian yang digunakan adalah metode eksperimen untuk menguji efektivitas POC Azolla terhadap tanaman pakcoy. Rancangan yang digunakan dalam penelitian ini adalah Rancangan Acak Lengkap (RAL). Pada percobaan ini terdapat 4 perlakuan dan 5 ulangan yaitu P0 = 0 ml/liter air (tanpa POC), P1 = POC 100 ml/l liter air, P2 = POC 150 ml/l liter air, P3 = POC 200 ml/l liter air. Parameter yang diamati adalah tinggi tanaman, jumlah daun tanaman, lebar daun tanaman dan bobot segar. Berdasarkan hasil penelitian yang telah dilakukan pada tanaman pakcoy menggunakan POC azolla dengan perlakuan konsentrasi P0=POC 0,0ml/liter air, P1=POC 100ml/liter air, P2=POC 150ml/liter air dan P3=POC sebanyak 200ml/liter air. Sehingga dapat disimpulkan bahwa pemberian POC azolla berpengaruh nyata terhadap semua parameter yaitu tinggi tanaman, lebar daun, jumlah daun, dan bobot segar tanaman pakcoy pada 3 MST sampai 6 MST. Kata kunci: Azolla pinnata, Pupuk Organik Cair, Brassica rapa L.